Electrochemical Properties of YSZ/GDC Bi-Layer Produced by One-Side Dip Coating Method for the Intermediate Temperature Solid Oxide Fuel Cell. (30th May 2017) - Kim, Sungmin; Jang, Inyoung; Kim, Chanho; Yoon, Heesung; Paik, Ungyu
Abstract : The Gadolinium Doped Ceria(GDC) diffusion barrier layer was formed on the Yttrium Stabilized Zirconia(YSZ) electrolyte to apply La0.6 Sr0.4 Co0.2 Fe0.8 O3 (LSCF) cathode system for lowering the operating temperature of Solid Oxide Fuel Cell. In this study, YSZ and GDC layers were coated by dip coating method which possibly coat one-side of anode substrate. Cu(NO3 )2 was infiltrated into pre-sintered substrate of anode and electrolyte as a sintering aid for lowering the co-firing temperature which was enough to produce dense electrolyte layer. LSCF-GDC cathode was coated on the GDC layer by screen printing method. The cells were operated at 600℃ and 650℃. The microstructures of the surface and cross-section were observed by Scanning Electron Microscopy (SEM). The ohmic and polarization resistance were measured by the Electrochemical Impedance Spectroscopy (EIS). The cell performance was measured by I-V curve observation.